Modelling the recovery of critical commercial services and their interdependencies on civil infrastructures. (6th September 2019) - Ni, Ni; Little, Richard G.; Sharkey, Thomas C.; Wallace, William
When an extreme event occurs in a specific area, the mere recovery of civil infrastructures is not enough to help recover local communities due to the cascading disruptions that can occur to supply chains of critical commercial services, whose operation and restoration is highly dependent on infrastructures. We build single-period, multi-commodity disruption models to examine the interdependencies between infrastructures and critical commercial services and predict the outages experienced by local communities after extreme events. We further build multi-period restoration models to select and schedule the restoration tasks after disruptive events with an objective to maximise the aggregated flows of utilities and commodities. We simulate scenarios of Categories 2, 3, 4 hurricanes and apply the models to a dataset of an artificial county with a population of half a million. We find that coordinated infrastructure restoration decisions with critical commercial services help improve community resilience, especially under relatively severe extreme events.